2017
DOI: 10.1002/adma.201703908
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐Controlled On/Off Switching of Ferromagnetism in Manganite Supercapacitors

Abstract: liquid devices via surface electrostatic doping [20][21][22][23] (as in electric doublelayer (EDL) capacitors) or via bulk ionic migration [12,[15][16][17][18][19] (akin to electrochemical batteries). Recently, robust ME effect was achieved in magnetic supercapacitors [24,25] via a surface electrochemical mechanism called pseudocapacitance. [26,27] By making use of interfacial redox reactions, pseudocapacitors concurrently benefit of fast, reversible charging/discharging processes (typical of EDL capacitors) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 38 publications
(80 reference statements)
1
48
0
Order By: Relevance
“…Subsequently, quantitative studies of ME coupling in epitaxial films of LSMO gated with DEME-TFSI IL revealed that the interfacial charging processes progressively move from electrostatic doping to surface redox pseudocapacitance upon increasing the external voltage. [42] In addition, the magnetic response was flexibly modulated in-phase or antiphase with respect to the induced surface charge by judiciously adjusting the applied bias voltage (see Figure 4b). By optimizing the surface to volume ratio of the devices, repeated suppression and recovery of ferromagnetism, with a T C shift of about 26 K, was demonstrated in ultrathin LSMO films (≈3 nm).…”
Section: Me Coupling Via Charge Carrier Dopingmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, quantitative studies of ME coupling in epitaxial films of LSMO gated with DEME-TFSI IL revealed that the interfacial charging processes progressively move from electrostatic doping to surface redox pseudocapacitance upon increasing the external voltage. [42] In addition, the magnetic response was flexibly modulated in-phase or antiphase with respect to the induced surface charge by judiciously adjusting the applied bias voltage (see Figure 4b). By optimizing the surface to volume ratio of the devices, repeated suppression and recovery of ferromagnetism, with a T C shift of about 26 K, was demonstrated in ultrathin LSMO films (≈3 nm).…”
Section: Me Coupling Via Charge Carrier Dopingmentioning
confidence: 99%
“…Recently, in IL-gated LSMO films, [42] a ΔM ≈ 54 emu cm −3 was attained by using a potential window ΔV ≈ 3 V, which, owing to the intrinsic small thickness (d ≈ 1 nm) of EDL capacitors, corresponds to an ultrahigh interfacial electric field E ≈ 30 MV cm −1 . Recently, in IL-gated LSMO films, [42] a ΔM ≈ 54 emu cm −3 was attained by using a potential window ΔV ≈ 3 V, which, owing to the intrinsic small thickness (d ≈ 1 nm) of EDL capacitors, corresponds to an ultrahigh interfacial electric field E ≈ 30 MV cm −1 .…”
Section: Comparison Of Technologically Relevant Me Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations